The HLA‐C*05 family allele – C*05:142. (21st June 2017) - Rowlands, J.; Climer, T.; Harvey, C.; Williams, L.; Darke, C.
Summary: The sequencing of exons 2–7 of a likely new HLA‐C*05 allele identified the second example of HLA‐C*05:142, in a male UK European, within a few months of the first example being found in Germany. C*05:142 differs from C*05:01:01:01 by a single base (395G>C) in exon 3 resulting in an amino acid substitution of R108P. Comprehensive serological HLA‐Cw5 typing, using 19 antisera, indicated that C*05:142 encodes a "normal" Cw5 specificity. Failure to identify the involvement of position 108 in published HLA‐C epitopes supported this assertion. The likely HLA class I C*05:142‐bearing haplotype is A*02:01~C*05:142~B*44:02. This new allele has a maximum frequency of 0.00001, in 34, 743 sequenced‐based typed subjects, contrasting with that of C*05:01 (allele frequency 0.10441), in our local, largely UK European, blood donors.